Ectoparasites on freshwater fishes at lower stream of Tuaran river, Sabah / Siti Nurshafiqah Hamdan - Hamdan, Siti Nurshafiqah (2016)
This study aims on the identification as well as provide information on the prevalence and intensity of ectoparasite in freshwater fishes at lower stream of Tuaran river, Sabah. A total of 42 individual from 5 different types of fish species were examined for ectoparasite from September to December of 2015 by using large and small net. The total number ectoparasite found was 311, with 4 type of ectoparasite found, which were nematode: Camillanus sp., Capillaha sp.; trematode: Opsthorcis sp.: protozoa: Piscinoodium sp., Trichordina sp., Gaussia sp.; and crustecea: Argulus sp. The highest number of ectoparasite found was nematode (269), followed by protozoa (41), trematode (8) and crustecea (3). All of the fishes captured and examined were positively infested by ectoparasite at 100% of prevalence, with 8.79 intensity in average. The most infested part in the fish body is ventral fin.